(untitled) (Communications in Computational Physics, 2020)
We investigate the hydrodynamic interactions of spherical colloidal nano particles and nano tetrahedra near a planar wall by means of molecular dynamics (MD) simulations of rigid particles within an all-atom solvent. For both spherical and nano-tetrahedral particles, we find that the parallel and perpendicular components of the local diffusion coefficient and viscosity, show good agreement with hydrodynamic theory of Faxén and Brenner. This provides further evidence that low perturbations from sphericality of a nanoparticle's shape has little influence on its local diffusive behaviour, and that for this particular case, the continuum theory fluid dynamics is valid even down to molecular scales.